2019
DOI: 10.1111/jfpe.13350
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidization of full‐fat ice cream mixes: Effects on rheology and microstructure

Abstract: Full-fat ice cream mixes with xanthan or locust bean gum (LBG) were subject to microfluidization at 220-250 MPa, then formed into ice cream. Particle size increased with average values increasing from 2.64 to 3.93 μm for xanthan mixes, and 2.51 to 4.72 μm for LBG mixes, suggesting interaction between polysaccharide and protein components that then aggregate at the lipid interface. Microfluidization marginally increased the shear-thinning behavior of mixes while dramatically increasing consistency, with xanthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The increase in fat contents in the ice cream contributes to the richness in mouthfeel and reduces ice crystal formation (Mostafavi, 2019). The higher fat content was attributed to the higher overrun, resulting in the low formation of ice crystals, and subsequently prolonging the shelf‐life of the ice cream (Cavender & Kerr, 2019). According to Akbari et al.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in fat contents in the ice cream contributes to the richness in mouthfeel and reduces ice crystal formation (Mostafavi, 2019). The higher fat content was attributed to the higher overrun, resulting in the low formation of ice crystals, and subsequently prolonging the shelf‐life of the ice cream (Cavender & Kerr, 2019). According to Akbari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ice cream is world-famous high-vital emulsified milk sweets made from air cells milk fat, colloidal protein, fortifiers (Ghandehari, Barzegar, Gavlighi, Sahari, & Mohammadian, 2020;Pintor, Escalona, & Totosaus, 2017), stabilizers, emulsifiers, sweeteners, and colors (Cavender & Kerr, 2020;Panwar, Shubhashini, & Kapoor, 2019). It is one of the most commonly offered and enjoyed by youngsters and other age people around the world (Ayar, Siçramaz, Ozturk, & Ozturk, 2018;Azari, Khomeiri, Ghafouri, & Aghajani, 2017;Caniyilmaz, Uçarkuş, & Karaman, 2016).…”
mentioning
confidence: 99%
“…The formulation of ice cream, process design, and effects of different microstructural elements, such as air cells, ice crystals, and fat globule clusters, are responsible for the properties of ice cream [ 9 , 19 ]. Several studies have shown that high shear force and microfluidization of fat replacers affect the physical and structural properties of frozen dairy products [ 19 , 20 ]. A few recent studies have also shown that homogenization at high pressure (200–400 MPa) decreases the need for stabilizers [ 21 ] and facilitates greater interaction between proteins and polysaccharides, thus leading to a stable network structure [ 22 ].…”
Section: Introductionmentioning
confidence: 99%